Impact of support to agriculture and forestry development project on maize productivity in South Sudan. (2017) - Tongun, Nixon James; Elepu, Gabriel
The government of South Sudan launched the Support to Agriculture and Forestry Development Project (SAFDP) in 2007, as one of the strategies to increase agricultural productivity and production. However, cereal productivity has generally remained low, resulting in persistent national food insecurity. Therefore, this study assessed the impact of SAFDP on productivity of maize in Central Equatoria. A survey of randomly selected sample of 80 SAFDP and 120 non-SAFDP maize farmers was done to collect primary data. A two-stage Heckman model was used to analyse data. Results obtained from the first stage of the model showed that household size and membership in a farmers' group positively influenced participation in SAFDP, whereas off-farm income had a negative effect. In the second stage model, it was found that the impact of SAFDP on maize productivity was positive. Nonetheless, measures need to be taken by stakeholders to upscale and ensure sustainability of SAFDP achievements.